Acoustic Transmitted Decellularized Fish Bladder for Tympanic Membrane Regeneration - Hong Chen; Hui Zhang; Guangjie Zhu; Long Cao; Chenjie Yu; Maoli Duan; Xiaoyun Qian; Xia Gao; Yuanjin Zhao (Research)
Developing advanced tissue-engineered membranes with biocompatibility, suitable mechanical qualities, and anti-fibrotic and anti-inflammatory actions is important for tympanic membrane (TM) repair. Here, we present a novel acoustically transmitted decellularized fish swim bladder (DFB) loaded with mesenchymal stem cells (DFB@MSCs) for TM perforation (TMP) repair. The DFB scaffolds are obtained by removing the cellular components from the original FB, which retains the collagen composition that favors cell proliferation. Benefitting from their spatially porous structures and excellent mechanical properties, the DFB scaffolds can provide a suitable microenvironment and mechanical support for cell growth and tissue regeneration. In addition, by loading mesenchymal stem cells on the DFB scaffolds, the resultant DFB@MSCs system exhibits remarkable anti-fibrotic and anti-inflammatory effects, together with the ability to promote cell migration and angiogenesis. In vivo experiments confirm that the prepared DFB@MSCs scaffolds can not only alleviate inflammatory response caused by TMP but also promote new vessel formation, TM repair, and hearing improvement. These features indicate that our proposed DFB@MSCs stent is a prospective tool for the clinical repair of TM.